The impact of physical exercise on adolescent social anxiety: the serial mediating effects of sports self-efficacy and expressive suppression - Jingtao Wu; Yanhong Shao; Jun Hu; Xinjuan Zhao (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective This study aims to investigate the impact of physical exercise on adolescent social anxiety and to elucidate the serial mediating roles of sports self-efficacy and expressive suppression within this context. Methods Utilizing a convenience random cluster sampling technique, this study surveyed 2500 primary and secondary school students across Sichuan, Guangdong, Shandong, Henan, and Jiangxi provinces. The survey utilized validated scales to assess physical exercise, sports self-efficacy, expressive suppression, and social anxiety among adolescents. Results The study revealed that: (1) Physical exercise has a significant negative correlation with social anxiety (r = -0.32, p < 0.01); (2) Sports self-efficacy significantly mediated the relationship between physical exercise and social anxiety, with an indirect effect of -0.15 (95% CI [-0.22, -0.09]); (3) Expressive suppression significantly mediated the relationship between physical exercise and social anxiety, with an indirect effect of -0.11 (95% CI [-0.17, -0.06]); (4) Sports self-efficacy and expressive suppression exerted a significant serial mediating effect on the relationship between physical exercise and social anxiety, with an indirect effect of -0.05 (95% CI [-0.08, -0.02]). Conclusion Physical exercise not only directly alleviates social anxiety in adolescents but also indirectly diminishes social anxiety through the enhancement of sports self-efficacy and the reduction of expressive suppression.